Exergy analysis for fuel reduction strategies in crude distillation unit - Izyan, Z.N. (Elsevier Ltd, 2014)
Inefficient furnaces and heat exchangers contribute to the depletion of fossil fuel problem due to higher fuel demand and higher carbon emission. The method of exergy analysis is applied to the furnace and crude preheat train (CPT) in a crude distillation unit (CDU) to determine performance benchmark of the system. This paper presents exergy analysis and strategies to reduce exergy loss through process modification. The highest exergy loss was found to be located at the inlet furnace. The proposed options for fuel reduction strategies are reduction of heat loss from furnace stack and overall cleaning schedule of CPT. The feasibility and economic analysis for both options are investigated. From the results, overall cleaning schedule of CPT contributes to the highest energy saving of 5.6. However, reduction of heat loss from furnace stack is the highest cost saving by about 6.4. Â© 2014 Elsevier Ltd.